Effect of black tea brew of Camellia sinensis on oestrous cycle of rats - Ratnasooriya, W.D.; Fernando, T.S.P. (My University, 2007)
This study examined the effects of black tea brew (BTB) of Camellia sinensis (L.) Kuntze (Family: Theaceae) on oestrous cycle using Sri Lankan high grown Dust grade No: 1 black tea and rats. Different doses of BTB (84 mg/ml, equivalent to 1.5 cups, mg/ml, equivalent to 3 cups and 501 mg/ml, equivalent to 9 cups) or 2 ml of water (control) were orally administered for 31 consecutive days and the oestrous cycle was monitored daily by vaginal smearing. The results showed that none of the doses of BTB significantly (P > 0.05) altered tlie percentage of occurrence of different stages of tlie oestrous cycle and its duration. It is concluded that daily ciironic administration of even high dose of BTB (equivalent to 9 cups) dose not disrupt the oestrous cycle of rats.